A review on integrating organ-on-chip microphysiological systems into early phase clinical trials for accelerated drug development - Tiwari, Gaurav; Thilagam, E.; Ramachandran, Dhani; V. Chinni, Suresh; Gajananrao Thakare, Vijay; S Hunge, Sudhir; Raghavendra Rao, Nidgurthi Guggulla (Journal of Neonatal Surgery, 2025)
Organ-on-chip (OOC) microphysiological systems have emerged as a promising alternative to traditional in vitro and animal models for drug development. These advanced platforms recreate the complex microenvironment and physiological functions of human organs, enabling more accurate predictions of drug efficacy and toxicity. The complex tissue-tissue interfaces, biochemical gradients, and mechanical cues found in vivo can be simulated effectively by OOC systems providing a powerful way for preclinical drug screening and testing. The integration of OOC systems into early phase clinical trials has the potential to revolutionize drug development by bridging the gap between preclinical studies and human clinical outcomes. This approach allows for the evaluation of drug candidates in a more physiologically relevant context, taking into account factors such as organ-specific responses, inter-individual variability, and disease-specific conditions. The incorporation of patient-derived cells and the development of multi-organ platforms further enhance the predictive power of OOC systems, enabling personalized medicine approaches and the assessment of systemic effects. However, challenges such as standardization, validation, scalability, and regulatory acceptance need to be addressed to fully realize the potential of OOC systems in clinical settings. As the knowledge on OOC systems advances, their integration into early phase clinical trials is expected to streamline the drug development process, reduce the reliance on animal testing, and accelerate the translation of basic research into safe and effective therapies for patients.